REORIENTASI HUKUM PEMILUKADA YANG MENSEJAHTERAKAN RAKYATNYA - Retno Saraswati (Jurnal Dinamika Hukum, 2014)
Currently, the implementation of direct election for regional leader (pilkada) is not able to create people's welfare. Even it tends to harm the morale of state officials and people as well. In regard to this, the state should take immediate political measures   to change direct local elections law into indirect one. In the perspective of a democratic state, indirect local election is in line with the concept of Indonesian democracy and also in accordance with   legal politics for people’s welfare. Thus, the election law is more meaningful to the Indonesian society.Keywords : Welfare, Indirect local elections, legal policy